Physics E-Book based on STEM Integrated Modelling Instruction in Circular Motion - Ndoa, Yohana Atwina Aspiranti; Jumadi (Universitas Pendidikan Ganesha, 2022)
Circular motion has many applications in everyday life. However, the circular motion of matter is one of the abstract concepts of physics. The use of e-books as a medium for learning physics can help students visualize abstract concepts. This study aims to develop and determine the feasibility of a STEM-integrated Modeling Instruction-based physics e-book on circular motion material for class X high school students. This research is research and development with the 4D development model. Physics e-books are assessed using a feasibility validation sheet for material and media experts. The product validators consist of two expert lecturers, four physics teachers, and two peer reviewers. Data collection techniques using interview techniques and questionnaires. The instrument used in collecting data is a questionnaire. Data analysis technique using descriptive analysis. The results showed that the average score for the developed e-book material was 3.92, which was included in the very high category. Meanwhile, the average value of e-book media is 3.97, which is included in the very high category. The results of the student response questionnaire were included in the very high category with an average value of 3.69. Thus, the physics e-book based on STEM-integrated Modeling Instruction is very suitable to be used as a medium for learning physics independently on circular motion material.